Apego parental y elección de pareja en adolescentes heterosexuales. - Basante López, Thalía Dayana (2025)
Parental attachment plays a key role in how teenagers grow emotionally and socially, and it affects how they choose their partners. This study aimed to explore the link between parental attachment and partner choice among heterosexual teens. It was necessary to conduct a review using trusted databases such as Scopus, Web of Science, ProQuest, PubMed, SpringerLink, Dialnet, Redalyc, and SciELO. Twenty-one studies were published in English and Spanish over the last 10 years. They were selected using the PRISMA guidelines to ensure reliability and relevance. We set clear rules for which studies to include and exclude, used search terms to guide our search, and assessed the quality of the studies using the CRF-QS review form. Results showed that the type of parental attachment has a strong effect on how teenagers choose their partners. Those with secure attachments often build relationships based on trust, good communication, and empathy. Teens with insecure styles (ambivalent, avoidant, or disorganized) often face relationship problems, emotional dependence, or avoid romantic relationships. Therefore, the quality of the parent-child bond shapes both emotional growth and how teenagers approach romantic bonds. These results highlight the importance of promoting secure attachment at home and provide useful information for mental health professionals who work with teens and their relationships.